Sleeping Beauty - A Legend in Progress Book review - Meisner, Nadine (Dance Books Ltd., Alton,Hampshire (UK), 2004)
A staunch defender of Petipa, Scholl explains how it was actually Tchaikovsky's ambitius score that enabled The Sleeping Beauty to survive against the odds. PALABRAS CLAVE: The Sleeping Beauty, Marius Petipa, Tchaikovsky, Russian ballets.
Dentro del apartado " Shelf Content".
Sleeping Beauty - A Legend in Progress. Tim Scoll, Yale University Press, 2004.